Permission : the new memoirist and the courage to create - Altman, Elissa (Godine, 2025)
"Who am I to tell my story? And how can we grant ourselves permission to write the stories we're compelled to tell when we've been told we shouldn't? Without fail, almost every writer--new or experienced--has faced dire questions of permission and story ownership: there is something that they want to write about, that they need to write about. Yet: they can't. They have been warned not to. They might be paralyzed with shame, threatened with shunning, chastened into silence. Even if what they need to write about has defined them and their worldviews. But what if they did? What if you did? After writing three critically-acclaimed memoirs and a decade of teaching memoir workshops at every level, Elissa Altman has helped students face the elephant in every writer's room: how to craft the stories that are most vital to them despite the voices that have told them not to. Permission is a master course, not only on how to craft memoir, but how to begin and keep going when you've been told you can't, and how to give yourself permission to transcend the fear that keeps vital stories from being written. We are the storytelling species; this book will inspire and guide all creatives to a place of transformation, of freedom from the constraints of shame and fear in all their forms, and to the understanding and recognition of the ethics of story-making, art-making, truth-telling, and creative soul-saving."--